Karakteristik ibu rumah tangga dengan HIV aids di rumah sakit umum - Tri Hastuti; Djaswadi Dasuki; Dhesi Ari Astuti (Universitas Aisyiyah Yogyakarta, 2017)
Abstract: The new paradigm of UNAIDS Global goal is Zero AIDS -related death, this can be achieved if patients come to HIV care and getARV therapy as soon as possible. The purpose of this study is to knowthe characteristics of housewives with HIV AIDS. This type of researchis descriptive. The sample of the study was housewives with HIV AIDSat Reproductive Health Center in Merauke with 30 respondents withtotal sampling. The majority of respondents were married (63.3%), aged 35 years (60.0%), highly educated (60.0%), receiving family support(90.0%) and complying with ARV (83.3%). Housewives with HIVAIDS at Merauke hospitals receive family support and are obedient totaking ARVs.